Methods for improving the lifetime performance of organic photovoltaics with low-costing encapsulation - Giannouli, Myrsini; Drakonakis, Vasileios M.; Savva, Achilleas; Eleftheriou, Polyvios; Florides, Georgios A.; Choulis, Stelios A. (My University, 2015)
Recent years have seen considerable advances in organic photovoltaics (OPVs), most notably a significant increase in their efficiency, from around 4 % to over 10 %. The stability of these devices, however, continues to remain an issue that needs to be resolved to enable their commercialization. This review discusses the main degradation processes of OPVs and recent methods that help to increase device stability and lifetime. One of the most effective steps that can be taken to increase the lifetime of OPVs is their encapsulation, which protects them from atmospheric degradation. Efficient encapsulation is essential for long-term device performance, but it is equally important for the commercialization of OPVs to strike a balance between achieving the maximum device protection possible and using low-cost processing for their encapsulation. Various encapsulation techniques are discussed herein, with emphasis on their cost effectiveness and their overall suitability for commercial applications.
Keywords: Encapsulation; Photochemistry; Photovoltaics; Reaction mechanisms; Stability